2020
DOI: 10.1080/02640414.2020.1823109
|View full text |Cite
|
Sign up to set email alerts
|

The influence of initial selection age, relative age effect and country long-term performance on the re-selection process in European basketball youth national teams

Abstract: The influence of initial selection age, relative age effect and country longterm performance on the re-selection process in European basketball youth national teams, Journal of Sports Sciences,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…As the NT consists of 12 players per tournament, the generally most used strategy seems to be leaning toward being more individualistic than in earlier studies in other sports (Güllich and Emrich, 2012;Barth et al, 2018). Similar differences between sports have been found when studying the number of players re-selected from 1 year to the next, where the re-selection was much higher in European NT basketball than in both German and Portuguese football Güllich, 2014;Kalén et al, 2020). These observed differences between sports could probably be related to the sport's popularity within specific countries, which might increase the number of licensed players in these sports and, consequently, the number of players available to be selected.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…As the NT consists of 12 players per tournament, the generally most used strategy seems to be leaning toward being more individualistic than in earlier studies in other sports (Güllich and Emrich, 2012;Barth et al, 2018). Similar differences between sports have been found when studying the number of players re-selected from 1 year to the next, where the re-selection was much higher in European NT basketball than in both German and Portuguese football Güllich, 2014;Kalén et al, 2020). These observed differences between sports could probably be related to the sport's popularity within specific countries, which might increase the number of licensed players in these sports and, consequently, the number of players available to be selected.…”
Section: Discussionsupporting
confidence: 51%
“…This allows us to compare the success of different selection strategies. Earlier basketball research has, for example, found a relationship between higher rates of re-selection in youth NT programs and better long-term performance of the senior NT (Kalén et al, 2020). A possible explanation discussed is that higher reselection rates might be an indication of better organization and clearer strategies within the program, which has been shown to lead to better performance (De Bosscher et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…RAEs occur not due to a single factor but rather due to a complex interaction of individual constraints (e.g., an individual's date of birth, maturation, and abilities), environmental constraints (e.g., talent promotion programs and coaches), and task constraints (e.g., the physical and physiological demands of the sport). This interaction leads to advantages for early-born players in athletically demanding sports such as track and field (Romann and Cobley, 2015), ice hockey (Nolan and Howell, 2010), handball (Wrang et al, 2018), basketball (López de Subijana and Lorenzo, 2018;Kalén et al, 2021), and soccer (Votteler and Höner, 2017;Hill et al, 2020a;Romann et al, 2020;Yagüe et al, 2020). This is particularly the case in team sports, where the specific demands of different playing positions can even be associated with different RAEs (Wattie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of international competitions for males, the impact seem less clear. International competitions are specialised high-performance sport contexts, and it might naturally be assumed that player selections would be influenced primarily by technical-tactical criteria , a player's initial selection age, or the country's long-term performance (Kalén et al, 2020). The lack of impact of RAE on performance in female competitions has been explained by lower biological and conditional differences among players from the same selection year (Konstantinos et al, 2018) and by the "depth of competition hypothesis" (Baker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%